Estudo experimental de um compósito de argamassa utilizando cinza e casca de arroz, aplicado em blocos de vedação - Ripoli Filho, Francisco (2019)
Sustainable Development is linked with a tripod: serving basic needs, shortage of natural resources and economic growth. In order to make it compatible with the principles of sustainability, this study focused on the investigation of mortar mix ratios (cement, sand, lime) with the addition disposable waste such as: rice husk (rice industry) and rice husk ashes (ceramic industry) to manufacture block work for civil construction. The materials used were classified based on physical, chemical, and mineralogic tests. The ratio methodology consisted in a partial substitution of small aggregates and cement by rice husk and rice husk ashes, respectively. Compressive strength tests were performed in cylindrical proof bodies measuring 50 mm x 100 mm with 1:3, 1:4, 1:6 and 1:8 ratios aged up to 180 days. A mechanical mixer as well as basic block molds (140mm x 290mm x 340mm) and its complementaries were developed using a 1:3,4 mortar proportion. In order to create hollow cavities, empty polyethylene terephthalate bottles (PET) were embedded into the blocks. The results herein reveal an average compressive strength of a 28 days aged mortar mix varying between 6,67 MPa to 5,56 MPa in a 1:3 ratio and between 1,90 MPa and 1,37 MPa in a 1:8 ratio with percentages of 0 to 20% of rice husk and 12% of rice husk ashes. The average compressive strength in 28 days aged blocks with 1 to 3 embedded bottles varied from 1,50 MPa to 2,60 MPa. Low walls presented compression strength average results of 0,87 MPa and efficiency factor ranging from 0,34 to 0,37 MPa when compared to the blocks. Further tests related to performance evaluation were also made in wall partitions such as: hard and soft body impact, suspended load resistance, water proofing, and thermal and acoustic performances. The analysis of the results reveal that the proposed block work is technically viable, presenting results that are compatible to the NBR 15.575:2013.